Are tumor size changes predictive of survival for checkpoint blockade based immunotherapy in metastatic melanoma?. Issue 1 (8th February 2019) - Wang, Meihua; Chen, Cong; Jemielita, Thomas; Anderson, James; Li, Xiaoyun (Nicole); Hu, Chen; Kang, S. Peter; Ibrahim, Nageatte; Ebbinghaus, Scot
Abstract : Background: In oncology clinical development, objective response rate, disease control rate and early tumor size changes are commonly used as efficacy metrics for early decision-making. However, for immunotherapy trials, it is unclear whether these early efficacy metrics are still predictive of long-term clinical benefit such as overall survival. The goal of this paper is to identify appropriate early efficacy metrics predictive of overall survival for immunotherapy trials. Methods: Based on several checkpoint blockade based immunotherapy studies in metastatic melanoma, we evaluated the predictive value of early tumor size changes and RECIST-based efficacy metrics at various time points on overall survival. The cut-off values for tumor size changes to predict survival were explored via tree based recursive partitioning and validated by external data. Sensitivity analyses were performed for the cut-offs. Results: The continuous tumor size change metric and RECIST-based trichotomized response metric at different landmark time points were found to be statistically significantly associated with overall survival. The predictive values were higher at Week 12 and 18 than those at Week 24. The percentage of tumor size changes appeared to have comparable or lower predictive values than the RECIST-based trichotomized metric, and a cut-off of approximately 10% tumor reduction appeared to be reasonable for predicting survival. Conclusions: An approximate 10% tumor reduction may be a reasonable cut-off for early decision-making while the RECIST-based efficacy metric remains the primary tool. Early landmark analysis is especially useful for decision making when accrual is fast. Composite response rate (utilizing different weights for PR/CR and SD) may be worth further investigation. Trial registration: Clinical trials gov, NCT01295827, Registered February 15, 2011; NCT01704287, Registered October 11, 2012; NCT01866319, Registered May 31, 2013.